Symbolism in Alfonso Cuarón’s A Little Princess: A Percian Semiotic Analysis - Nurhaliza, Siti; Hariani, Safitri (JOURNAL OF LANGUAGE, 2026)
This study explores the use of symbolism in Alfonso Cuarón's film A Little Princess (1995). Using a qualitative descriptive method and semiotic analysis based on Charles Sanders Peirce's theory, this research identifies how symbolic elements function as representations of the main character's emotional journey, personal transformation, and inner resilience. The findings reveal three types of symbols based on Peirce's classification. Natural symbols include weather and atmosphere (cold weather and snow, the smell of warm food, colorful sky like a peacock's tail). Conventional symbols consist of color symbols (black dress, dark tones, bright colors during the birthday scene), object symbols (Emily the doll, birthday cake, the locket), and nature symbols (colorful sky, cold weather, warm wind). Singular symbols include imagination as a shield, the magic circle, and the attic transformation. These findings demonstrate that Cuarón employs symbolism not only for visual storytelling but also as a narrative tool to express deeper emotional and psychological meanings. The symbols effectively convey Sara Crewe's struggle against injustice and her ability to endure adversity through imagination and empathy, enriching the film's themes of loss, identity, hope, and resilience.